Diaphragm and preparation method thereof, battery and electric equipment
By introducing fiber coatings into the separator and embeding ceramic coatings, the problem of insufficient adhesion during the circulation of the existing separator is solved, and higher peel strength, high temperature resistance and electrolyte adsorption ability are achieved, extending the cycle life of the battery and improving safety performance.
Patent Information
- Application Number
- CN202510156144.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-06-27
AI Technical Summary
During the circulation process, the existing coated diaphragms may cause material dropping and microcracks due to the small adhesion between the base film and the coating, resulting in a decrease in the cycle life of the battery cell and an increase in internal resistance.
The diaphragm structure is adopted including a base film, a fiber coating and a ceramic coating. The fiber coating is embedded in the ceramic coating to improve the heat shrinkage resistance of the ceramic coating and improve the overall performance of the membrane through the high temperature resistance of the fiber material.
It improves the peel strength of the diaphragm, high temperature resistance and electrolyte adsorption ability, thereby extending the battery cycle life, reducing internal resistance, and improving the battery safety performance.
Smart Images

Figure CN120221928A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the technical field of batteries, and particularly relates to a separator and its preparation method, a battery, and an electrical device. Background Art
[0002] With the increasingly wide application of lithium-ion batteries, the demand for lithium-ion batteries is continuously increasing, and the public's attention to the safety and cycle life of batteries is also getting higher and higher. The domestic production of separators has also increased significantly, mainly wet separators. Currently, the application proportion of coated separators as the mainstream separator products in lithium batteries is continuously increasing. However, during the cycling process, the coated separators may experience material shedding due to the small adhesion between the base film and the coating, resulting in microcracks, which leads to a decrease in the cycle life of the battery cell and an increase in internal resistance. Therefore, the related preparation technologies of separators need to be further improved. Summary of the Invention
[0003] This application aims to solve at least one of the technical problems in the related technologies to some extent. For this purpose, this application provides a separator with high peel strength, high liquid retention ability, or good high-temperature resistance, and its preparation method, a battery, and an electrical device.
[0004] In a first aspect of this application, a separator is provided, including:
[0005] A base film;
[0006] A fiber coating disposed on at least one surface of the base film, including a fiber material;
[0007] A ceramic coating disposed on the surface of the fiber coating away from the base film.
[0008] Thus, the separator has high peel strength and high-temperature resistance, thereby improving the cycle performance and safety performance of the battery using it.
[0009] In some embodiments, at least a part of the fiber coating is embedded in the ceramic coating. This can improve the thermal shrinkage resistance of the ceramic coating.
[0010] In some embodiments, the fiber material includes at least one of polyimide fiber, lithium fluoride fiber, and aramid fiber. Thus, the material source is wide and the cost is low.
[0011] In some embodiments, the aspect ratio of the fiber material is 30 - 900; in some other embodiments, the aspect ratio of the fiber material is 50 - 400; the diameter of the fiber material is 0.03 μm - 0.2 μm; in some other embodiments, the diameter of the fiber material is 0.1 μm - 0.15 μm. When the aspect ratio and diameter of the fiber material are within the above ranges, it is beneficial to improve the peel resistance of the separator.
[0012] In some embodiments, the areal density of the fiber coating is 0.1 g / m 2 ~1.0 g / m 2 , and the thickness of the fiber coating is 0.2 μm to 0.5 μm. Thereby, the liquid retention capacity, peel strength and heat shrinkage resistance of the separator can be further improved.
[0013] In some embodiments, the fiber coating further includes an additive, and the additive includes at least one of polyacrylic acids and their copolymers, polyacrylates and their copolymers, polyvinyl alcohols and their copolymers, polyvinylpyrrolidone and its copolymers, carboxymethyl cellulose and its derivatives, polyvinylidene fluoride and its copolymers, polytetrafluoroethylene, polyimide, polyamide, polysulfone, acrylonitrile polymers. Thereby, the material source is wide and the cost is low. Adding it to the fiber slurry is beneficial to improving the adhesiveness of the fiber slurry.
[0014] In some embodiments, based on the total mass of the fiber coating, the mass content of the additive is 1% to 5%. Thereby, it is beneficial to save costs and improve the adhesiveness of the fiber slurry.
[0015] In some embodiments, the base film includes at least one of polypropylene (PP), polyethylene (PE), and a composite film of polypropylene and polyethylene. Thereby, the material source is wide and the cost is low.
[0016] In some embodiments, the ceramic coating includes at least one of alumina, boehmite, calcium oxide, silica, titanium dioxide, zirconium dioxide, magnesium oxide, zinc oxide, barium oxide, lithium aluminum titanium phosphate, and lithium lanthanum zirconium oxide. Thereby, the material source is wide and the cost is low.
[0017] In some embodiments, the D50 range of the ceramic particles in the ceramic coating is 0.3 μm to 1 μm. Thereby, it is beneficial to improve the peel force of the ceramic coating.
[0018] A second aspect of the present application provides a method for preparing a separator, including: formulating a fiber slurry from a fiber material and a solvent; coating the fiber slurry on at least one surface of a base film and performing a first drying to form a fiber coating; coating a ceramic slurry on the surface of the fiber coating away from the base film and performing a second drying to form a ceramic coating, thereby obtaining the separator.
[0019] The above preparation method of the present application has a simple operation process. In the actual operation process, no new dedicated heating equipment needs to be introduced, and it is easy to be industrially produced on a large scale.
[0020] In some embodiments, the solvent includes at least one of deionized water, ethanol, acetone, and N-methylpyrrolidone. Thereby, the material source is wide and the cost is low.
[0021] In some embodiments, the coating method includes roll coating.
[0022] A third aspect of the present application provides a battery, including the separator described in the first aspect of the present application or the separator prepared by the method described in the second aspect of the present application. Thus, the battery has high cycle performance and safety performance.
[0023] A fourth aspect of the present application provides an electrical device, including the battery described in the third aspect of the present application. The electrical device has all the features and advantages of the battery described above, which will not be elaborated here one by one. Description of the Drawings
[0024] Figure 1 is a schematic cross-sectional view of the separator according to an embodiment of the present application.
[0025] Reference numerals: 1 - base film, 2 - ceramic coating, 3 - fiber coating. Detailed Embodiments
[0026] Embodiments of the present application will be described in detail below. Examples of the embodiments are shown in the drawings. The embodiments described below with reference to the drawings are exemplary and are intended to explain the present application, and should not be construed as a limitation of the present application.
[0027] A first aspect of the present application provides a separator. Referring to Figure 1 , the separator includes: a base film 1, a ceramic coating 2, and a fiber coating 3; wherein, the fiber coating is disposed on at least one surface of the base film and includes a fiber material, and the ceramic coating is disposed on the surface of the fiber coating away from the base film. In the present application, a fiber coating is innovatively added between the base film and the ceramic coating. On the one hand, the addition of the fiber coating forms a tight connection with the base film through chemical bonds, significantly improving the peel force of the ceramic coating without significantly increasing the cost and the thickness of the separator. On the other hand, since the fiber coating has high temperature resistance, it can improve the thermal shrinkage resistance of the separator. At the same time, the addition of the fiber coating increases the specific surface area and improves the adsorption of the electrolyte, which is beneficial to improving the cycle performance and safety performance of the battery cell.
[0028] In some embodiments, at least a part of the fiber coating is embedded in the ceramic coating. This can improve the thermal shrinkage resistance of the ceramic coating.
[0029] In some embodiments, the fiber material includes at least one of polyimide fiber, lithium fluoride fiber, and aramid fiber. Thus, the material source is wide and the cost is low.
[0030] In some embodiments, the aspect ratio of the fiber material is 30 to 900, and can be, for example, 30, 60, 90, 120, 150, 200, 300, 400, 500, 600, 700, 800, or 900, etc.; in some other embodiments, the aspect ratio of the fiber material is 50 to 400. Herein, the aspect ratio of the fiber material refers to the ratio of the length to the diameter of the fiber material. The aspect ratio has a great influence on the properties of the fiber material, and the mechanical properties of the fiber material are optimal when the aspect ratio is within a suitable range. The specific test method for the aspect ratio only requires measuring the length L and diameter D of the fiber, and then calculating the value of L / D. For the determination of the fiber length, there are mainly two methods: the microscope method and the measurement method. The operating steps of the microscope method are to place the fiber on the scale plate of the microscope, observe and select the longest fiber, make the scale on the scale plate correspond to the fiber by focusing, and then slide the scale plate until the fiber breaks, and record the distance between the lower end points as the length of the fiber. The operating steps of the measurement method are to fix one end of the fiber at the starting position of the measuring instrument, and then pull the other end of the fiber to make it pass through the measuring instrument, and record the time or length when the fiber passes through the instrument to obtain the length of the fiber. For the determination of the fiber diameter, it can be measured by the microscope method. The operating steps are to place the fiber on the stage of the microscope, make the fiber clearly visible by focusing, and observe and record the diameter of the fiber.
[0031] In some embodiments, the diameter of the fiber material is 0.03 μm to 0.2 μm, and can be, for example, 0.03 μm, 0.05 μm, 0.08 μm, 0.1 μm, 0.13 μm, 0.15 μm, 0.18 μm, or 0.2 μm, etc.; in some other embodiments, the diameter of the fiber material is 0.1 μm to 0.15 μm.
[0032] When the aspect ratio and diameter of the fiber material are within the above ranges, it is beneficial to improve the peel resistance of the separator.
[0033] In some embodiments, the areal density of the fiber coating is 0.1 g / m 2 ~1.0 g / m 2 , and can be, for example, 0.1 g / m 2 , 0.2 g / m 2 , 0.4 g / m 2 , 0.6 g / m 2 , 0.8 g / m 2 or 1.0 g / m 2etc.; the thickness of the fiber coating is 0.2 μm to 0.5 μm, and can be, for example, 0.2 μm, 0.3 μm, 0.4 μm or 0.5 μm, etc. Among them, the areal density is the mass per unit area of a substance with a specified thickness. The specific test method is as follows: Cut a 100 mm × 100 mm diaphragm sample, weigh the mass of each diaphragm with an electronic balance and record it as M, with the unit of mg. The areal density of the fiber coating can be calculated by M / 10, with the unit of g / m 2 . If the areal density of the fiber coating is too small, the liquid retention capacity, peel strength and thermal shrinkage performance of the diaphragm cannot be improved; if the areal density of the fiber coating is too large or the thickness is too thick, it will hinder the passage of lithium ions and cause a decrease in electrical conductivity.
[0034] In some embodiments, the fiber coating further includes an additive, and the additive includes at least one of polyacrylic acids and their copolymers, polyacrylates and their copolymers, polyvinyl alcohols and their copolymers, polyvinylpyrrolidone and its copolymers, carboxymethyl cellulose and its derivatives, polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride copolymers, polyimides, polyamides, polysulfones, acrylonitrile polymers. Thus, the material source is wide and the cost is low, which is beneficial to improving the adhesiveness of the fiber slurry.
[0035] In some embodiments, based on the total mass of the fiber coating, the mass content of the additive is 1% to 5%, and can be, for example, 1%, 2%, 3%, 4% or 5%, etc.
[0036] In some embodiments, the base film includes at least one of polypropylene (PP), polyethylene (PE), and a composite film of polypropylene and polyethylene. Thus, the material source is wide and the cost is low.
[0037] In some embodiments, the ceramic coating includes at least one of alumina, boehmite, calcium oxide, silicon dioxide, titanium dioxide, zirconium dioxide, magnesium oxide, zinc oxide, barium oxide, lithium titanium aluminum phosphate, and lithium lanthanum zirconium oxide. Thus, the material source is wide and the cost is low.
[0038] In some embodiments, the D50 of the ceramic particles in the ceramic coating ranges from 0.3 μm to 1 μm, and can be, for example, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm, etc. Among them, the D50 particle size refers to the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. This means that 50% of the particles have a particle size larger than this value, and at the same time, 50% of the particles have a particle size smaller than this value. Therefore, D50 is also called the median diameter or median particle size. The specific test method for D50 is the laser particle size analyzer method. The specific steps are to first configure a certain concentration of dispersion solvent, then weigh the sample to be tested with a balance, pour it into a beaker, add a certain amount of dispersion solvent, stir well to disperse evenly, select the corresponding SOP template on the laser particle size analyzer, perform background measurement on the optical system. After the background measurement is completed, pour the sample into the circulation cell to make the light obscuration reach the preset range, ultrasonicate for a certain time, click the start measurement button, measure 3 times and automatically take the average value for recording, and finally read the average value of the D50 test. When D50 is within the above range, it is beneficial to improve the peel strength of the ceramic coating.
[0039] The second aspect of this application proposes a method for preparing a separator, including:
[0040] S1: Prepare a fiber slurry by mixing a fiber material and a solvent.
[0041] In some embodiments, the solvent includes at least one of deionized water, ethanol, acetone, and N-methylpyrrolidone (NMP). Thus, the material source is wide and the cost is low.
[0042] As an example, the fiber material and an auxiliary agent can be added to deionized water to prepare a fiber slurry.
[0043] S2: Coat the fiber slurry on at least one surface of the base film, perform a first drying to form a fiber coating.
[0044] In some embodiments, the coating method includes roll coating. Specifically, existing roll coating equipment can be used to adjust the coating parameters to coat the fiber slurry on the surface of the base film with the required areal density and thickness. After coating, age for 24 h. Subsequent operations such as coating the ceramic slurry, coating the glue, drying, and winding are no different from the traditional separator preparation method.
[0045] It should be noted that the orientation of the fiber material in the separator does not need to be specially controlled. Whether the radial direction is parallel to the base film, or between parallel and perpendicular, or perpendicular can all play a role in improving the adhesion between the base film and the ceramic coating, and the acting force gradually increases.
[0046] As an example, the prepared fiber slurry can be coated on the surface of the base film, and the surface density and thickness are controlled to the required values, and then left to dry in the air for a certain period of time to form a fiber coating.
[0047] S3: Coat the ceramic slurry on the surface of the fiber coating away from the base film, perform secondary drying to form a ceramic coating, and obtain the separator.
[0048] As an example, the ceramic slurry can be continuously coated on the surface of the fiber coating, and then left to dry in the air for a certain period of time to form a ceramic coating.
[0049] In the above method of the present application, a step of coating a fiber coating is added before the traditional step of coating the ceramic slurry. Instead of the direct contact between the original ceramic coating and the base film, it becomes base film - fiber coating - ceramic coating. The fiber coating plays a role similar to the "foundation" for building a house for the ceramic coating. The fiber material partially inserts into the ceramic coating, so the peel strength is greatly enhanced. At the same time, the addition of the fiber material increases the specific surface area, improves the adsorption of the electrolyte, and the fiber material itself has high heat resistance, thus playing a role in resisting thermal shrinkage.
[0050] In the third aspect of the present application, a battery is proposed, including the separator described in the first aspect of the present application or the separator prepared by the method described in the second aspect of the present application. Thus, the battery has high cycle performance and safety performance.
[0051] It can be understood that there is no particular limitation on the specific type of the battery. It can be a primary battery, a secondary battery (including but not limited to lithium-ion batteries, sodium-ion batteries, etc.); the shape of the battery can be a cylindrical battery, a square battery or any other shape battery, etc. Classified by the outer packaging, the battery can be a hard-shell battery, a soft-pack battery, etc.
[0052] Generally, in addition to the separator described in the present application, the battery also includes a positive electrode sheet, a negative electrode sheet and an electrolyte. Among them, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly through a winding or lamination process, and the electrode assembly and the electrolyte can be accommodated in the outer packaging. During the charge and discharge process of the battery, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly playing a role in preventing short circuit between the positive and negative electrodes, and at the same time allowing ions to pass through.
[0053] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer provided on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, a conductive agent, and a binder. The positive electrode current collector may include a metal foil. For example, the metal foil may be an aluminum foil. The positive electrode active material may include lithium nickel cobalt manganate (NCM811), lithium nickel cobalt manganate (613), lithium cobaltate, lithium iron phosphate, lithium manganate, lithium nickel manganate, lithium-rich manganese-based material, or positive electrode active materials commonly used in the art. The conductive agent may include acetylene black, single-walled carbon nanotubes, and conventional materials in the art. The binder may be polyvinylidene fluoride (PVDF) and conventional materials in the art.
[0054] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material, a thickening agent, a conductive agent, and a binder. Among them, the negative electrode current collector may use a metal foil. For example, the metal foil may be a copper foil. The negative electrode active material may include artificial graphite, natural graphite, silicon-containing carbon-based composite material, lithium-containing metal composite material, lithium metal material, and negative electrode active materials commonly used in the art. The thickening agent may be sodium carboxymethyl cellulose (CMC-Na) and conventional materials in the art. The conductive agent may be acetylene black and conventional materials in the art. The binder may be styrene-butadiene rubber and conventional materials in the art.
[0055] The fourth aspect of the present application proposes an electrical device, including the battery described in the third aspect of the present application. This electrical device has all the features and advantages of the battery described above, and will not be elaborated one by one here.
[0056] In some embodiments, the battery can be used as the power source of the electrical device or as the energy storage unit of the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc., but not limited thereto.
[0057] The embodiments of the present application will be described in detail below.
[0058] Example 1
[0059] (1) Prepare a fiber slurry with a solid content of 30% by mixing deionized water, polyimide fibers (aspect ratio of 200, diameter of 0.1 μm), and carboxymethyl cellulose (the mass ratio of polyimide fibers to carboxymethyl cellulose is 25:1);
[0060] (2) Coat the prepared fiber slurry on the surface of the PE base film, and control the areal density to be 0.3 g / m2 , with a thickness of 0.5 μm;
[0061] (3) After coating, age for 24 h. Coat the alumina ceramic slurry (D50 is 1 μm) on the surface of the fiber coating, control the thickness to be 2 μm, and obtain the separator after drying.
[0062] Example 2
[0063] (1) Prepare a fiber slurry with a solid content of 30% by mixing deionized water, polyimide fibers (aspect ratio is 200, diameter is 0.1 μm), and carboxymethyl cellulose (the mass ratio of polyimide fibers to carboxymethyl cellulose is 25:1).
[0064] (2) Coat the prepared fiber slurry on the surface of the PE base film, control the areal density to be 0.9 g / m 2 , with a thickness of 0.5 μm;
[0065] (3) After coating, age for 24 h. Coat the alumina ceramic slurry (D50 is 1 μm) on the surface of the fiber coating, control the thickness to be 2 μm, and obtain the separator after drying.
[0066] Example 3
[0067] (1) Prepare a fiber slurry with a solid content of 30% by mixing N-methylpyrrolidone, lithium fluoride fibers (aspect ratio is 900, diameter is 0.2 μm), and polysulfone (the mass ratio of lithium fluoride fibers to polysulfone is 25:1).
[0068] (2) Coat the prepared fiber slurry on the surface of the PE base film, control the areal density to be 0.5 g / m 2 , with a thickness of 0.5 μm;
[0069] (3) After coating, age for 24 h. Coat the alumina ceramic slurry (D50 is 0.3 μm) on the surface of the fiber coating, control the thickness to be 2 μm, and obtain the separator after drying.
[0070] Example 4
[0071] (1) Prepare a fiber slurry with a solid content of 30% by mixing ethanol, aramid fibers (aspect ratio is 300, diameter is 0.03 μm), and polyacrylate and its copolymer (the mass ratio of aramid fibers to polyacrylate and its copolymer is 25:1).
[0072] (2) Coat the prepared fiber slurry on the surface of the PE base film, control the areal density to be 0.1 g / m 2 , with a thickness of 0.2 μm;
[0073] (3) After coating, age for 24 h. Coat the surface of the fiber coating with silica ceramic slurry (D50 is 0.5 μm), control the thickness to be 2 μm, and obtain a separator after drying.
[0074] Example 5
[0075] The difference from Example 1 is that the diameter of the polyimide fiber is adjusted to 0.3 μm, and the other parameters remain unchanged.
[0076] Example 6
[0077] The difference from Example 1 is that the areal density of the fiber coating is adjusted to 0.05 g / m 2 , and the other parameters remain unchanged.
[0078] Example 7
[0079] The difference from Example 1 is that the areal density of the fiber coating is adjusted to 1.5 g / m 2 , and the thickness is adjusted to 2 μm, and the other parameters remain unchanged.
[0080] Comparative Example 1
[0081] The difference from Example 1 is that the separator is not coated with fiber slurry.
[0082] The experimental conditions of Examples 1-7 and Comparative Example 1 refer to Table 1.
[0083] Table 1 Experimental Conditions
[0084]
[0085] Perform relevant tests on the separators of Examples 1-7 and Comparative Example 1. The experimental results are shown in Table 2:
[0086] (1) Wettability: Through electrolyte diffusion test (the better the wettability of the separator, the faster the electrolyte diffusion rate and the larger the electrolyte diffusion area). The specific test steps are as follows. Lay the separator flat on a smooth and clean glass plate in a fume hood. Use a disposable dropper to suck the electrolyte and quickly drop a drop of electrolyte on each sample at the same time. Start timing at the same time. Take a photo after 1 min of timing, and compare the electrolyte diffusion areas of each separator. The larger the area, the better the electrolyte infiltration performance.
[0087] (2) Peel force and tensile strength: Test by Instron 3365 universal tensile machine.
[0088] The peel strength test is to bond the coated surface of the coated separator with a stainless steel plate using an adhesive to prepare a bonded specimen. Then, the coated separator is reversed by 180°. Next, the bonded specimen is peeled open from the bonded opening at a specified rate using a universal tensile testing machine. In this way, the coated separator is gradually separated from the glass slide along the length direction of the bonded surface. During the separation process, the coating of the coated separator is completely adhered from the base film by the adhesive, thus separating the coating from the base film. The force value when the coating and the base film are separated is automatically obtained by the testing machine, and the peel strength between the coating and the base film of the coated separator is calculated based on this value.
[0089] The tensile strength test is to cut the separator into strips with a width of 15 mm along the TD and MD directions. Select a relatively flat 10 cm section from the strips and make marks. Clamp the two ends with marks on the tooling fixtures of the tensile machine, set the parameters, and click to measure to obtain the test results.
[0090] (3) Air permeability: Tested by an Asahi air permeability tester.
[0091] The air permeability test is to intercept 3 square separators with a size of 100 mm×100 mm at intervals of 150 mm. Use a Wang Yan type air permeability tester to test and record the time it takes for 100 mL of air to pass through an area of 6.45 cm 2 of the separator under a pressure of 1.21 kPa. Take the average value of the 3 test results as the air permeability of the separator.
[0092] (4) Thermal shrinkage: Experiment is carried out using a forced air oven.
[0093] The thermal shrinkage test is to cut the separator into standard sample blocks with a size of 100 mm×100 mm, mark the sample model and the TD and MD directions, and then use a steel ruler to mark a range of 80 mm×80 mm. Take two layers of pollution-free printing paper and staple them into a paper fixture. Place the paper fixture loaded with the sample into a constant temperature drying oven that has reached the test temperature, and start timing. After the test time ends, take out the paper fixture containing the sample and measure the size in an environment with the same state conditions as the specimen.
[0094] Table 2 Experimental results
[0095]
[0096] The positive electrode sheet prepared from LiFePO4, PVDF powder, and Super-P powder in a mass ratio of 8:1:1 was used as the positive electrode, and the lithium sheet was used as the negative electrode. They were assembled into a 2025-type button battery with the separators of the comparative examples and examples. The assembled lithium-ion button battery was tested for rate performance and cycle performance on a Blue Electric CT2001A type electrochemical tester. The first charge and discharge were carried out at 0.2C, and the cut-off voltage was 4.2V. After the first charge, it was left standing for 10 minutes, and then charge and discharge tests were carried out 5 times each at current densities of 0.2C, 0.5C, 1C, 2C, and 5C. The cycle performance of the battery could be obtained by performing 100 constant current charge and discharges on the battery at 0.5C. The test temperature was room temperature, and the voltage range was 2.5V to 4.2V. The experimental results are shown in Table 3.
[0097] Table 3 Experimental Results
[0098]
[0099]
[0100] From the experimental results of Examples 1 to 7 and Comparative Example 1, it can be seen that compared with the comparative example, when the fiber coating was applied to the separator in the examples, the physical and chemical properties and electrical properties of the separator were improved, and when the fiber material diameter was in the range of 0.03μm to 0.2μm, the fiber coating surface density was in the range of 0.1g / m 2 ~1.0g / m 2 range or the thickness of the fiber coating was in the range of 0.2μm to 0.5μm, the comprehensive performance of the separator was the best. When the fiber coating was not applied to the separator, the liquid retention amount of the whole separator decreased, the peel force and tensile strength decreased, the thermal shrinkage performance decreased significantly, and the button cell cycle life decreased significantly. It can be seen that adding a fiber coating between the base film and the ceramic coating in this application can not only improve the peel force of the separator, reduce the risk of cyclic material loss, but also improve the electrolyte infiltration, increase the tensile strength, reduce the thermal shrinkage, improve the physical and chemical properties of the separator, and at the same time be beneficial to high-rate discharge and cycle life, and improve the electrochemical performance of the separator.
[0101] In the description of this specification, the description referring to terms such as "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of this application. In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in a suitable manner in any one or more embodiments or examples. In addition, without contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples.
[0102] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and should not be construed as limiting the present application. Those of ordinary skill in the art can make changes, modifications, substitutions, and variations to the above embodiments within the scope of the present application.
Claims
1. A diaphragm, characterized in that: include: Basement membrane; a fiber coating layer, the fiber coating layer being disposed on at least one side surface of the base film and comprising a fiber material; A ceramic coating is disposed on a surface of the fiber coating away from the base film.
2. The diaphragm according to claim 1, characterized in that The fiber coating is at least partially embedded in the ceramic coating.
3. The diaphragm according to claim 1, characterized in that The fiber material includes at least one of polyimide fiber, lithium fluoride fiber, and aramid fiber; and / or The aspect ratio of the fiber material is 30 to 900, preferably 50 to 400; and / or The diameter of the fiber material is 0.03 μm to 0.2 μm, preferably 0.1 μm to 0.15 μm; and / or The surface density of the fiber coating is 0.1 g / m 2 ~1.0g / m 2 ; and / or The thickness of the fiber coating is 0.2 μm to 0.5 μm.
4. The diaphragm according to claim 1, characterized in that The fiber coating also includes an additive, which includes at least one of polyacrylic acid and its copolymers, polyacrylate and its copolymers, polyvinyl alcohol and its copolymers, polyvinyl pyrrolidone and its copolymers, carboxymethyl cellulose and its derivatives, polyvinylidene fluoride and its copolymers, polytetrafluoroethylene, polyimide, polyamide, polysulfone, and acrylonitrile polymers.
5. The diaphragm according to claim 4, characterized in that Based on the total mass of the fiber coating, the mass content of the auxiliary agent is 1% to 5%.
6. The diaphragm according to claim 1, characterized in that The base film comprises at least one of polypropylene, polyethylene, or a composite film of polypropylene and polyethylene; and / or The ceramic coating comprises at least one of aluminum oxide, boehmite, calcium oxide, silicon dioxide, titanium dioxide, zirconium dioxide, magnesium oxide, zinc oxide, barium oxide, lithium aluminum titanium phosphate, and lithium lanthanum zirconium oxide; and / or The D50 range of the ceramic particles in the ceramic coating is 0.3 μm to 1 μm.
7. A method for preparing the diaphragm according to any one of claims 1 to 6, characterized in that: include: preparing fiber slurry by mixing fiber material and solvent; Applying the fiber slurry on at least one side of the base film and performing a first drying to form a fiber coating; A ceramic slurry is coated on the surface of the fiber coating layer away from the base membrane, and a second drying is performed to form a ceramic coating layer, thereby obtaining the separator.
8. The method according to claim 7, characterized in that The solvent comprises at least one of deionized water, ethanol, acetone, and N-methylpyrrolidone; and / or The coating method includes roller coating.
9. A battery, characterized in that: The invention comprises the diaphragm according to any one of claims 1 to 6 or the diaphragm prepared by the method according to any one of claims 7 to 8.
10. An electrical device, characterized in that: A battery comprising the battery of claim 9.